'I worry about getting it wrong and looking like a silly billy': does explicit classroom-based strategy intervention change pupils' attitudes towards speaking in the modern foreign languages classroom?. Issue 3 (4th May 2023) - Thompson, Nicholas Philip; Mutton, Trevor
ABSTRACT: A number of factors among schoolchildren in England are currently contributing to poor attitudes towards speaking in the modern foreign languages (MFL) classroom. Although multiple explicit strategy-based instruction (SBI) intervention studies have appeared in recent years, very few studies have focused on its effect on oral skills and, in particular, pupils' attitudes towards speaking in the target language (TL). From the small pool of SBI investigations into schoolchildren whose first language (L1) is English, there is some evidence of success among boys in particular. The present quasi-experimental, two-cycle action research and development study of beginner (Year 7) and intermediate (Year 10) learners of L2 French ( N = 148) investigated the impact of 12 hours of strategy intervention training on attitudes towards TL speaking skills in the MFL classroom in an all-boys selective secondary school in England. To assess the impact of the intervention, a mixed-methods approach was adopted; data were captured via questionnaires, lesson observations and interviews. In Cycle 2, pupils navigated the 'Strategy Island Map', an innovative tool to track their strategy use when speaking in the TL. Results suggest that explicit SBI improved attitudes towards speaking among both age groups. Implications for practice and suggestions for future research are discussed.